Peningkatan Kualitas Video Conference Menggunakan Packet Priority - Johan Ericka Wahyu Prakasa (LPPM STIKI MALANG, 2022)
Video conferencing is one of the technologies widely used for learning during the Covid-19 pandemic. UIN Maulana Malik Ibrahim Malang is one of the universities that implements online learning and has a video conference platform that is connected to an electronic learning system (e-learning). However, not all students can access a smooth internet connection. This causes a decrease in the quality of video conferencing that interferes learning process. This study seeks to find ways to improve the quality of video conferencing on a limited internet connection. This research use the packet priority technique at the router to manipulate the packet queue. Video conference data packet will be prioritized upon another application data. The results of the research show that manipulating the queue of data packets on a computer network can improve the quality of video conferencing on a limited bandwidth from the delay and jitter parameters between 20% to 30%. Meanwhile, packet loss shows 0%, but packet retransmission is quite a lot in the scenario without packet priority, especially at bandwidth < 3Mbps. The results of this study indicate that the priority manipulation of data packets has an impact on reducing lag / lost information when the video conference process takes place, especially at bandwidth < 3Mbps.